An Evaluation of the Aspects of Arrangement of Customary Villages in Maluku Province - Siska Giofana Mapusa (Journal Research of Social Science, Economics, and Management, 2023)
This study aims to determine whether Maluku Province regulations have regulated arrangements for customary villages in a consistent manner in accordance with statutory regulations. Furthermore, this study will analyze and evaluate one of the objects of regional legal products, namely the Regional Regulation of the Province of Maluku Number 16 of 2019 concerning the Arrangement for Customary Villages. This study was conducted using normative methods. The data used in this study consisted of primary data and secondary data. All data were analyzed using qualitative methods. The results of this study were presented in a descriptive analysis report. The results showed that regional legal products in Maluku Province have formulations that were not in accordance with the higher laws and regulations and have legal uncertainties in the implementation of customary village arrangements in Maluku Province.